2012
DOI: 10.17221/6346-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of red clover and lucerne forages for ruminants estimated by in vitro and in vivo digestibility methods

Abstract: ABSTRACT:The aim of this study was to determine the nutrient and energy levels of red clover and lucerne forage. Investigation of forage at different maturity stages of three growths was carried out by chemical analysis, in vitro and in vivo digestibility methods. Generally, maturation caused a significant increase in fibre fractions. With the increasing maturity of forage samples the in vivo, in vitro, and calculated in vivo (in vivo calcul ) digestibilities of organic matter (OM) linearly decreased. The in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…The results obtained in the current study are generally in agreement with those reported by Homalka et al (2012) for cell wall components of red clover cultivars at various stage of development. Balancing the appropriate level and type of non-structural and structural carbohydrates is a major challenge in formulating ruminant diets.…”
Section: Protein and Carbohydrate Degradability Profilesupporting
confidence: 92%
“…The results obtained in the current study are generally in agreement with those reported by Homalka et al (2012) for cell wall components of red clover cultivars at various stage of development. Balancing the appropriate level and type of non-structural and structural carbohydrates is a major challenge in formulating ruminant diets.…”
Section: Protein and Carbohydrate Degradability Profilesupporting
confidence: 92%
“…Forage exhibited increasing lignification with rising plant maturity (ADL = 43.9 and 64.9 g/ kg DM for the first and second mitres, respectively). This trend has been cited in several publications (Rinne and NykÓnen, 2000;Homolka et al, 2012). The GE of the estimated samples had an average of 19.7 MJ/kg DM.…”
Section: Resultssupporting
confidence: 70%
“…No significant difference between DMD or between TDP of the different fractions was found. However, the fractionated white clover leaves were more concentrated with respect to CP content, demonstrating that, in a low fibre‐containing legume such as white clover,, the extra processing needed to isolate leaves is only necessary to secure a product with the highest possible protein content.…”
Section: Discussionmentioning
confidence: 99%